SUFFERING AND SOVEREIGNTY OF GOD ACCORDING TO JOHN PIPER AND ITS IMPLICATION FOR THE CHURCH TODAY - Woyesa, Tigist (European journal of philosophy, culture and religion, 2021)
Purpose: The purpose of this paper is to analyze the theology of suffering from a biblical perspective by using literature review as methodology. Methodology: One of the foundational evangelical presuppositions for theological research is that Scripture is divinely authored and is therefore without error, and authoritative for our faith and practice. Findings: The study found that suffering is biblical and should be expected by all Christians as they are not exempted from it, unlike prosperity teaching. Suffering has the purpose of refining and maturing our faith. Further, it is to display the greatness of the glory of the grace of God. Unique Contribution to theory and practice: Therefore, it is recommended for Christians to depend on God at all seasons by asking for wisdom and grace from him. So in this paper, the relationship between suffering and the sovereignty of God and its implication to the church will be discussed with a particular focus on John Piper's work